Epistula 86 Once Again: Agriculture and Philosophy in Seneca's Moral Letters. - Zainaldin, James L. (Classical Philology, 2019)
Literary criticism to the book "Epistula 86" by Lucius Annaeus Seneca is presented. It explores the Seneca's trip to the villa of Scipio Africanus. During his visit Seneca has spoken with Aegialus, who taught him how to transplant a tree, no matter how old, so as to make it productive again and the remainder of the letter consists of instructions for transplanting.